Everyday Creativity and the Healthy Mind Dynamic New Paths for Self and Society - Richards, Ruth (Palgrave Studies in Creativity and Culture, 2018)
"Our health and wellbeing depend on the kind of innovative thinking found in abundance in this book." - Judith V Jordan, Director, Jean Baker Miller Institute, Wellesley College, USA "At times confessional, intimate, joyous, funny, playful, challenging, direct, provocative, deep, and wide-ranging, this book is always engaging, run-through with erudition, and just 'pops' with ideas on every page." - Nick Wilson, Reader in Creativity, Arts & Cultural Management, King's College London, UK. Formerly, professional vocalist in early music ensembles and an arts manager/ promoter "Dr. Richards has given us a book that combines scholarly examination of creativity research with encouragement to all of us who may at times unknowingly incorporate creativity into our everyday activities." - Antoinette Jakobi, Associate Professor of Psychiatry, University of Rochester Medical School, USA As human beings we all have creative potential, a quality essential to human development and a vital component to healthy and happy lives. However this may often remain stifled by the choices we make, or ways in which we choose to live in our daily lives. Framed by the "Four Ps of Creativity" - product, person, process, press - this book offers an alternative understanding of the fundamentals of ordinary creativity. Ruth Richards highlights the importance of "process", circumventing our common preoccupation with the product, or creative outcome, of creativity. By focusing instead on the creator and the creative process, she demonstrates how we may enhance our relationships with life, beauty, future possibilities, and one another. This book illustrates how our daily life styles and choices, as well as our environments, may enable and allow creativity; whereas environments not conducive to creative flow may kill creative potential. Also explored are questions of 'normality', beauty and nuance in creativity, as well as creative relationships.